Development and evaluation of a bead-based Multiplexed Fluorescent ImmunoAssay (MFIA) for detection of antibodies to Salmonella enterica serogroup B and C1 in pigs - Andresen, L.O (BioMed Central Ltd, 2022)
Background: Since 1995, a surveillance program for Salmonella has been applied in the Danish pig industry in order to reduce cases of human salmonellosis. The objective of this study was to develop a bead-based Multiplexed Fluorometric ImmunoAssay (MFIA) as an improved serological surveillance method compared to the Salmonella mix ELISA, which has been the national reference immunoassay in the Danish Salmonella surveillance program for about 20 years. Results: An MFIA for detection of antibodies to Salmonella serogroup B and C1 was developed and optimized with regard to coupling of beads with Salmonella lipopolysaccharide antigens and establishing suitable assay conditions. The Salmonella MFIA was validated by testing sera from experimentally infected pigs as well as field sera from non-infected and infected pig herds, and by comparing to results from the Salmonella mix ELISA, which was run in parallel. Sensitivity and specificity was evaluated using receiver operating curve analysis showing an area under curve for the serogroup B and C1 MFIA of 0.984 and 0.998, respectively. The Salmonella MFIA was shown to detect more antibody-positive samples in seropositive herds compared to the Salmonella mix ELISA, and Bayesian statistics confirmed that the MFIA had a considerably higher sensitivity (94.5%) compared to the mix ELISA (75.1%). The assay specificity was slightly lower for the Salmonella MFIA (96.8%) compared to Salmonella mix ELISA (99.5%). Coupled beads were stable for at least 1 year at 4˚C, and MFIA reproducibility and repeatability of the Salmonella MFIA were acceptable. Results from proficiency tests also indicated that the Salmonella MFIA was more sensitive than the Salmonella mix ELISA and that they had similar specificity. Conclusions: A bead-based MFIA for simultaneous detection of porcine serum antibodies to Salmonella enterica serogroup B and C1 was developed and implemented in the Danish porcine serological Salmonella surveillance program in 2018. The Salmonella MFIA can distinguish, as opposed to the Salmonella mix ELISA, between antibodies to serogroup B and C1 and the MFIA shows considerably better sensitivity. © 2022, The Author(s).